Validity and Practicality of AI-Integrated Interactive Chemical Equilibrium E-Module Based on Structured Inquiry to Improve Students’ Critical Thinking Ability - Adi Susanto; Minda Azhar; Yerimadesi; Umar Kalmar Nizar; Salsabilla Putri Serli (Jurnal Penelitian Pendidikan IPA, 2026)
Chemical equilibrium is one of the chemistry topics that is abstract and complex, often causing difficulties for learners in understanding the concepts and their applications. This study aimed to determine the validity and practicality level of an Artificial Intelligence (AI)-integrated interactive e-module on chemical equilibrium based on structured inquiry to improve students’ critical thinking ability. This study was a Research and Development (R&D) using the Plomp development model, which includes the Preliminary Research and Development or Prototyping Phase, without conducting the Assessment Phase. The results show that the developed e-module obtained a validation score of 0.92 (valid category) and a very high practicality level of 97%. The findings indicated that the AI-integrated, structured-inquiry-based interactive e-module on chemical equilibrium to improve Phase F students’ critical thinking ability is valid and practical.